The Effect Of Substituting Tofu Waste Flour (Glycine Max l. Merrill) In The Production Of Dried Farfalle On Consumers’ Acceptance - Devi Rukmana,; Mariani,; Guspri Devi Artanti, (Jurnal Sains Boga, 2022)
Abstract The aim of this research is to determine the effect of substituting tofu waste flour in the production of dried Farfalle on consumers’ acceptance. This research was conducted in Pastry and Bakery Laboratory in Vocational of Culinary Education, State University of Jakarta. This was an experimental research. Based on assessment of acceptance test to 30 semi trained panel about organoleptic aspects, dried farfalle with tofu waste flour substitution were well accepted. The score of the 5 aspects, namely color (raw and cooked), taste, aroma, and texture, were all in the category of quite like to like. The result of organoleptic test was analyzed with Friedman test in significance level α = 0,05 proved that on the aspect of raw and cooked pasta color there are effects of tofu waste flour substitution in the production of dried farfalle on consumers’ acceptance. Meanwhile, the hypothesis testing on taste, aroma, and texture shows that there is no effects of tofu waste flour substitution in the production of dried Farfalle on consumers’ acceptance. Keywords : Consumers’ Acceptance, Dried Pasta, Farfalle, Tofu Waste Flour.